2011
DOI: 10.1002/art.30111
|View full text |Cite
|
Sign up to set email alerts
|

HLA–DRB1*0407 and *1304 are risk factors for scleroderma renal crisis

Abstract: Objective. To examine the predictive role of HLA genetic markers in scleroderma renal crisis (SRC), beyond the known clinical correlates, in a large population of patients with systemic sclerosis (SSc).Methods. SSc patients from the Scleroderma Family Registry and DNA Repository, the Genetics versus Environment in Scleroderma Outcomes Study, and the rheumatology division registry at the University of Texas Health Science Center at Houston were included in the study. Relevant clinical data were obtained by char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 14 publications
2
34
2
3
Order By: Relevance
“…In the past year, Nguyen et al [34] reported HLA markers that have a predictive role in scleroderma renal crisis. They included 1519 SSc patients, 90 of whom had scleroderma renal crisis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In the past year, Nguyen et al [34] reported HLA markers that have a predictive role in scleroderma renal crisis. They included 1519 SSc patients, 90 of whom had scleroderma renal crisis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several risk factors with a predictive value were established: duration of SSc onset of less than four years, higher incidence of progressive skin thickening prior to renal involvement, new development of anemia and cardiac involvement (pericardial effusion or congestive heart failure) [32]. Detection of anti-RNA polymerase III antibodies displays a strong risk marker for the presence of SRC, whereas the presence of anti-topoisomerase and anti-centromere antibodies in scleroderma indicates a favorable disease course [33]. In addition, a case control study revealed a significant positive association between long-lasting high-dose corticosteroid treatment (≥15 g/d) and the onset of SRC [34].…”
Section: Introductionmentioning
confidence: 99%
“…95 100 101 103 RNA polymerase III Anti-RNA polymerase III is another systemic sclerosis specific antibody that is associated with diffuse cutaneous involvement and is strongly linked to the occurrence of scleroderma renal crisis (odds ratios ranging from 5 to 17.5). [104][105][106] Therefore, patients with systemic sclerosis and anti-RNA polymerase III antibodies should be monitored closely for new onset hypertension. In addition, oral glucocorticoids should be used with caution in patients with systemic sclerosis, especially those with anti-RNA polymerase III antibodies, because these drugs have been linked to the development of scleroderma renal crisis.…”
Section: Emerging Biomarkersmentioning
confidence: 99%